2015
DOI: 10.4103/1008-682x.150846
|View full text |Cite
|
Sign up to set email alerts
|

Percent free prostate-specific antigen is effective to predict prostate biopsy outcome in Chinese men with prostate-specific antigen between 10.1 and 20.0 ng ml−1

Abstract: Percent free prostatic-specific antigen (%fPSA) has been introduced as a tool to avoid unnecessary biopsies in patients with a serum PSA level of 4.0–10.0 ng ml−1, however, it remains controversial whether %fPSA is effective in PSA range of 10.1–20.0 ng ml−1 in both Chinese and Western population. In this study, the diagnostic performance of %fPSA and serum PSA in predicting prostate cancer (PCa) and high-grade PCa (HGPCa) was analyzed in a multi-center biopsy cohort of 5915 consecutive Chinese patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Their subsequent study found that a cutoff value of %fPSA was 0.25 in patients over the age of 60 years, with a relatively low diagnostic accuracy. 29 In our study, we used the previously reported %fPSA cutoff value of 0.16. 30 It could be used for biopsy decision-making at first, but due to its low NPV, it is insufficient to provide a final clinical decision.…”
Section: Discussionmentioning
confidence: 99%
“…Their subsequent study found that a cutoff value of %fPSA was 0.25 in patients over the age of 60 years, with a relatively low diagnostic accuracy. 29 In our study, we used the previously reported %fPSA cutoff value of 0.16. 30 It could be used for biopsy decision-making at first, but due to its low NPV, it is insufficient to provide a final clinical decision.…”
Section: Discussionmentioning
confidence: 99%